2019
DOI: 10.1088/1361-6560/ab02cd
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised respiratory signal extraction from ungated cardiac magnetic resonance imaging at rest and during exercise

Abstract: We propose and evaluate a method to estimate a respiratory signal from ungated cardiac magnetic resonance (CMR) images. Ungated CMR images were acquired in 5 subjects who performed exercise at different intensity levels under different physiological conditions while breathing freely. The respiratory motion was estimated by applying principal components analysis (PCA). A sign correction procedure was developed to correctly define inspiration and expiration, based on either tracking of the diaphragmatic motion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Linear PCA was used both in this work and URE, 13 but there are differences between the two approaches: (i) In our method, the images are pre‐filtered to suppress the cardiac motion and (ii) the temporal mean is subtracted before applying linear PCA. Our directionality determination procedure, which is the major contribution of this work, is distinct from URE.…”
Section: Discussionmentioning
confidence: 99%
“…Linear PCA was used both in this work and URE, 13 but there are differences between the two approaches: (i) In our method, the images are pre‐filtered to suppress the cardiac motion and (ii) the temporal mean is subtracted before applying linear PCA. Our directionality determination procedure, which is the major contribution of this work, is distinct from URE.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has previously demonstrated the feasibility, reliability and clinical utility of CMR to quantify cardiac volumes and function during exercise. [74][75][76] The assessment of myocardial function during exercise will allow us to investigate whether the duration and intensity of long-term endurance exercise affect LV and RV functional reserve.…”
Section: Carotid Artery Ultrasoundmentioning
confidence: 99%
“…The motion information is already present in the RT cine images; therefore, the respiratory signal can be extracted directly using data-driven methods. Various strategies to extract the respiratory signal from RT cine data have been developed [2,3,4]. Among them, PCA-based methods [3,4] are particularly appealing because they are fast and independent of the slice orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies to extract the respiratory signal from RT cine data have been developed [2,3,4]. Among them, PCA-based methods [3,4] are particularly appealing because they are fast and independent of the slice orientation. However, due to the nature of PCA, the extracted signal has an arbitrary sign, which means that the maximal signal could refer either to the inspiration or expiration phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation